2006
DOI: 10.1097/01.bpo.0000230333.73286.06
|View full text |Cite
|
Sign up to set email alerts
|

Locking Versus Standard Plates for Allograft Fixation After Tumor Resection in Children and Adolescents

Abstract: Results of this investigation suggest that use of locking plates for allograft-host junction fixation is associated with improved union rates and less need for additional operations when compared with standard compression plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Union was achieved in 16/18 segments in a mean time of 12 weeks [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Union was achieved in 16/18 segments in a mean time of 12 weeks [6][7][8][9][10][11][12][13][14][15][16].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally three patients developed nonunion in the former group, out of whom two healed after autogenous bone grafting, with the third patient requiring a revision of plate for persistent nonunion 16). Another study from India reported the union time of one-month following fixation of pathologic fracture and 120 days after limb salvage surgery 17).…”
Section: Discussionmentioning
confidence: 99%
“…23 Interestingly, altering the mechanism of internal fixation when using frozen allografts by using locking plates instead of compression plates has improved clinical success. 24 Vascularized free fibular grafts have been successful in managing allograft fractures after limb salvage surgery for malignant bone tumors. 25 There are some oncologic orthopaedic surgeons who combine vascularized fibula grafting with allograft reconstruction in the primary tumor operation.…”
Section: Autograft Bonementioning
confidence: 99%